ANALISIS PEMBINAAN PEGAWAI BADAN PUSAT STATISTIK KABUPATEN KARAWANG - Gista Septiyanti; Uus Md Fadli (JOURNAL SAINS STUDENT RESEARCH, 2024)
Employee development at the Karawang Regency Central Statistics Agency (BPS) is essential in improving organizational performance and the quality of statistical data. This research aims to explore the importance of direction, motivation, supervision and coordination in employee development and identify the challenges faced in its implementation. The research method used is a qualitative pattern, namely a pattern that focuses on in-depth study. Data collection techniques can be done through observation, interviews and documentation. The research results show that effective direction, motivation through performance rewards, continuous supervision, and coordination between employees play a crucial role in improving professionalism and work quality. However, challenges such as a lack of quality training and suboptimal performance evaluations still hamper coaching efforts. In conclusion, a more structured strategy in training, supervision, and strengthening communication between departments is needed to overcome this challenge.